2014
DOI: 10.2322/tastj.12.po_2_29
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effects of Density, Thickness and Heat Load on Heat Shielding Performance of Phenolic Carbon Ablators Using a One-Dimensional Ablation Analysis Code

Abstract: The effects of density, thickness and heat load upon the heat shield performance of the lightweight phenolic carbon ablators named LATS (Lightweight Ablator series for Transfer vehicle Systems) were examined quantitatively for both arc-heated test and re-entry heating conditions using a one-dimensional ablation analysis code. Thermal conductivity values of the ablator were tuned based on the arc-heated test results by matching the calculated temperatures to the measured data. Main findings are: (1) For both he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Mathematical model of ablation, input data for the ablation analysis and the analysis conditions for the parametric study are shown in the following sections. 10,11) A one-dimensional computer code for charring ablation and thermal response analysis was used to calculate the heat resistant performance of the LATS ablators. The code was developed for simulation of one-dimensional transient thermal behavior of charring materials, and was successfully applied to the LATS ablators under the heating environments of arc-heated test.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mathematical model of ablation, input data for the ablation analysis and the analysis conditions for the parametric study are shown in the following sections. 10,11) A one-dimensional computer code for charring ablation and thermal response analysis was used to calculate the heat resistant performance of the LATS ablators. The code was developed for simulation of one-dimensional transient thermal behavior of charring materials, and was successfully applied to the LATS ablators under the heating environments of arc-heated test.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] The in-depth governing equations for onedimensional charring ablator response are energy, mass continuity, and decomposition equations, and are expressed by…”
Section: Mathematical Model Of Ablationmentioning
confidence: 99%
See 3 more Smart Citations